Discrepancies between Parent and Teacher Reports of Motor Competence in 5-10-Year-Old Children with and without Suspected Developmental Coordination Disorder - Li Ke; Anna L. Barnett; Yun Wang; Wen Duan; Jing Hua; Wenchong Du (MDPI AG, 2021)
Parents and teachers have knowledge of children's daily motor performance yet may make different judgments about the levels of competence observed at home and school. The current study aimed to examine the discrepancies between parent and teacher reports using the Movement ABC-2 Checklist and the Developmental Coordination Disorder Questionnaire (DCDQ) on children with and without suspected Developmental Coordination Disorder (DCD). The Movement ABC-2 Test was administered to 1276 children aged 5-10 years in China. The Movement ABC-2 Checklist and DCDQ were completed by both parents and teachers of all children. A total of 172 children achieving a score below the 15th percentile on the Movement ABC-2 Test were identified as children with suspected DCD. Both parents and teachers showed suitable agreement in judging children's motor competence but low sensitivity in identifying children with DCD. Parent scores of children's motor competence were more closely associated with test performance scores compared to teacher scores. Teachers tended to over-rate children's motor competence. The motor difficulties identified by parents were associated with low Movement ABC-2 Test scores on Manual Dexterity and Balance components, while motor difficulties identified by teachers were associated with the Balance component only. The results demonstrated discrepancies between parent and teacher reports, suggesting the importance of using a range of measures to identify and describe motor difficulties in children.